2017
DOI: 10.1002/anie.201709750
|View full text |Cite
|
Sign up to set email alerts
|

Utilising Sodium‐Mediated Ferration for Regioselective Functionalisation of Fluoroarenes via C−H and C−F Bond Activations

Abstract: Pairing iron bis(amide) Fe(HMDS) 2 with Na-(HMDS) to form new sodium ferrate base [(dioxane) 0.5 ·NaFe-(HMDS) 3 ]( 1)e nables regioselective mono and di-ferration (via direct FeÀHexchange) of awide range of fluoroaromatic substrates under mild reaction conditions.T rapping of several ferrated intermediates has provided key insight into how synchronised Na/Fecooperation operates in these transformations.F urthermore,u sing excess 1 at 80 8 8Cs witches on ar emarkable cascade process inducing the collective twof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
2
40
1
Order By: Relevance
“…[5] By expanding the scope of AMMM beyond main‐group chemistry, we recently reported that pairing the iron(II) amide Fe(HMDS) 2 (HMDS=N{SiMe 3 } 2 ) with NaHMDS in the same coordination compound allows regioselective ferration (Fe‐H exchange) of a wide range of fluoroarenes. [6] Since sodium is mandatory for the metallation to occur, these reactions can be described as examples of alkali‐metal‐mediated ferration (AMMFe) processes. This reactivity is surprising considering the lower polarity of Fe−N vs. Na−N bonds, which is why applications of iron amides in metallation are rare.…”
mentioning
confidence: 99%
“…[5] By expanding the scope of AMMM beyond main‐group chemistry, we recently reported that pairing the iron(II) amide Fe(HMDS) 2 (HMDS=N{SiMe 3 } 2 ) with NaHMDS in the same coordination compound allows regioselective ferration (Fe‐H exchange) of a wide range of fluoroarenes. [6] Since sodium is mandatory for the metallation to occur, these reactions can be described as examples of alkali‐metal‐mediated ferration (AMMFe) processes. This reactivity is surprising considering the lower polarity of Fe−N vs. Na−N bonds, which is why applications of iron amides in metallation are rare.…”
mentioning
confidence: 99%
“…poorly modelled toluene solvent molecule, for which a significant distortion is not likely to be real. Compared with genuine cases of in-plane angular distortions in this way, our own results (Maddock et al, 2018) are indeed extreme, the smallest C-C-Fe angle in these ferrated benzene derivatives being 97 with others not much larger. Clearly the cause here is a significant secondary FeÁ Á ÁN interaction that may be regarded as incipient covalent bonding leading to angular distortions also at the Fe and N atoms.…”
Section: Angular Distortions In and Around Benzene Ringsmentioning
confidence: 44%
“…Compound 2 is then the first example of a sodium aluminate of stoichiometry [NaAlMe 3 (L)] n with phenoxo-imino ligands and one of the very few reported. The influence of Na···F interactions has been acknowledged not only in the structure but also in the reactivity of heterometallic sodium species as it has been reported for metallated reactions [55].…”
Section: Resultsmentioning
confidence: 99%